Post-COVID isolated subclavian artery dissection with multiple cerebral infarctions - Alloush, Taha K.; Alloush, Adel T.; Marzouk, Fayez; Abdulghani, Khaled O.; Shokri, Hossam M. (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Background Coronavirus disease 2019 (COVID-19) is a pandemic disease which predominantly affects the respiratory system with high critical care mortality and morbidity, yet it also causes multiple organs dysfunction in affected patients. There is a strong evidence that it increases the susceptibility of cerebrovascular strokes in such patients. Besides this prothrombotic complication, arterial dissection can be one of its mechanisms increasing the risks of stroke. Case presentation Herein, we report a case of spontaneous isolated subclavian artery dissection in a COVID-19 patient. Sixty-one-year-old female presented with spontaneous isolated subclavian artery dissection without any traumatic events nor history of connective tissue disorders. She had left upper limb ischemia followed by cerebellar, thalamic and occipital infarctions. Whether this patient’s subclavian artery dissection was triggered by exaggerated inflammatory response or arteriopathy secondary to COVID-19 remains speculative. Conclusions Nonetheless, arterial dissection can be one of its complications, it is essential for treating physicians to be attentive for the diversity of COVID-19 clinical manifestations.